Immunohistochemical analysis of epidermal growth factor receptor as a predictive biomarker in lung adenocarcinoma – A cross-sectional study of 33 cases on computed tomography-guided core needle biopsy specimens - Sajeeb Mondal,; Sankha Chatterjee,; Mrinal Sikder,; Rajashree Pradhan, (Asian Journal of Medical Sciences, 2024)
Background: Lung cancer is the second most common cause of cancer in all ages and both genders and is the leading cause of cancer death. Two major groups of lung cancers are – small cell lung carcinoma (SCLC) and non-SCLC (NSCLC). Due to discovery of driver mutation such as epidermal growth factor receptor (EGFR) mutation in NSCLC, the paradigm of lung cancer therapy has shifted from cytotoxic platinum based therapy to tyrosine kinase inhibitor (TKI) therapy. In this study, we have analyzed EGFR expression in NSCLC by immunohistochemistry (IHC) and studied the response to TKI therapy in terms of progression free survival (PFS) and overall survival (OS). Aims and Objectives: In this study, we have retrospectively analyzed the EGFR overexpression in adenocarcinoma of lung in core needle biopsy (CNB) specimen by IHC analysis and correlated with the therapeutic response and survival rate (OS and PFS) in lung carcinoma patients. Materials and Methods: We have analyzed retrospectively EGFR expression in lung adenocarcinoma cases (computed tomography-guided CNB specimen) by IHC. In our study, we have used monoclonal primary antibodies against two most common EGFR mutations, that is, L858R point mutation and E 746–A 750 deletion. Results: Out of 33 cases, EGFR expression was seen in 28 cases. For EGFR expression assessment by IHC, both cytoplasmic and/or membranous staining taken into consideration. EGFR positivity was interpreted only when >10% tumor cells having 2+ or more intensely staining pattern. The response to TKI therapy in terms of PFS and OS was also studied. Conclusion: IHC analysis of EGFR mutation using specific antibodies has extremely high specificity with good sensitivity. Use of targeted therapy in the form of TKI in EGFR positive lung adenocarcinoma has high response rate and long duration of survival (PFS and OS) with acceptable toxicity profile in contrast to the conventional therapy.